Environment mapping and air purification system for vehicular and brick kiln emissions - Rahman, Md. Mubassir; Sakib, Farhan Anees; Tanvir, Nahid (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2020.